Psychological approaches to obesity in young adults: state of the art - Alves, Rafaela; Petitjean, Hugues; Druzhinenko-Silhan, Daria (Frontiers in Nutrition, 2024)
Abstract: Background: Obesity has become a significant health concern among young adults aged 18-35 years. Addressing this issue is crucial, and exploring psychological treatments and perspectives specifically for this population is essential. Methods: This literature review examines psychological treatments for obesity in young adults over the past decade. It focuses on interventions and discussions particularly relevant to this age group. Discussion: Research on obesity often overlooks young adults, with most interventions primarily focusing on weight loss and neglecting emotional aspects. Cognitive-behavioral approaches are commonly used for self-regulation and motivation, but psychodynamic perspectives remain underutilized. While group-based methods lack a detailed analysis of benefits, hybrid approaches demonstrate higher engagement compared to technology-only interventions. There is a notable gap in tailoring obesity interventions to meet the unique needs of young adults during this transitional life phase. It's imperative to shift the focus from merely weight loss to a broader consideration of psychological, emotional, and unconscious factors. Integrating group modalities with psychodynamic approaches might offer additional benefits. Conclusion: This review highlights the need for further research into the psychological well-being of young adults with obesity. A more comprehensive approach is required to address their distinct needs and psychological factors.